Anecdotes of sustainable intensification - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Supported by USAID as part of the US Government’s Feed the Future initiative, the Africa RISING project is working to create opportunities for smallholder farm households to move out of hunger and poverty through sustainably intensified farming systems that improve food, nutrition, and income security. This seven minute video showcases how the project interventions are touching farmer's lives in Northern Ghana.